Interaksi antara Herbal dan Antidiabetik Oral pada Penderita Diabetes Melitus: Tinjauan Mekanisme Aksi - Nurul Hafizha Shidiqiyah; Shofiatulfuadah Retnaningrum Herlaesa; Okta Piola; Nayla Nur Azkia Hariadi; Nur Basmalah; Mukarromah Dita Putri; Indah Laily Hilmi (Journal of Pharmaceutical and Sciences, 2026)
The increasing use of herbal products among patients with diabetes mellitus highlights the need for a clear understanding of their potential interactions with oral antidiabetic drugs (OADs). Such interactions may be synergistic or may pose risks, particularly hypoglycemia. To identify the mechanisms underlying interactions between herbal products and OADs and to assess their relevance in the management of type 2 diabetes mellitus. A literature search was conducted through Google Scholar, PubMed, and ScienceDirect using keywords related to herbal products, oral antidiabetic drugs, and drug interactions. Articles were selected based on inclusion criteria (2015–2025, original research, human subjects with type 2 diabetes mellitus or animal models, English or Indonesian language, and involving OADs) and relevant exclusion criteria. The most frequently reported interactions were pharmacodynamic, particularly the combination of Cinnamomum verum, Curcuma longa, and Momordica charantia with metformin or sulfonylureas, which enhanced insulin sensitivity, activated AMPK, or stimulated insulin secretion, potentially increasing the risk of hypoglycemia. Pharmacokinetic interactions were also identified, such as ginseng-induced modulation of the OCT1 transporter, which may influence metformin accumulation. Several other herbal products, including Aloe vera, demonstrated glucose-lowering activity; however, evidence of direct interactions with OADs remains limited, suggesting a primarily supportive role. Interactions between herbal products and oral antidiabetic drugs have important clinical implications, as they may alter both therapeutic efficacy and safety. Close monitoring and patient education are essential, alongside further research to clarify interactions that remain insufficiently documented.